2006
DOI: 10.1111/j.2006.0030-1299.14720.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of stochastic processes in producing nested patterns of species distributions

Abstract: Nestedness has received considerable attention in community ecology and conservation biology from both theoretical and empirical perspectives. This has lead to the creation of various metrics and null models to analyze nested subsets, all of which rely on the random placement of species to assess significance. However, if immigration and extinction are the processes that underlie species distributions on island systems, then null models might be better determined on the basis of randomly placed individuals. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 43 publications
(68 reference statements)
0
66
0
1
Order By: Relevance
“…Ultimately, whilst we can not confi rm what determined the species clusters in the secondary forest, we can not exclude that stochastic processes, such as the random placement of individuals, could produce the observed patterns of species distributions (Higgins et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Ultimately, whilst we can not confi rm what determined the species clusters in the secondary forest, we can not exclude that stochastic processes, such as the random placement of individuals, could produce the observed patterns of species distributions (Higgins et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Total species numbers m and total sites numbers n per matrix were also sampled from uniform distributions (10 B m B 100 and 10 B n B 100). This sampling protocol produced random matrices with relatively high matrix fills that were moderately to strongly nested due to passive sampling (Higgins et al 2006). In the second type of random matrix (M E ), species occurrences were sampled from a uniform random distribution until a randomly chosen number of species (again 10 B m B 100 and 10 B n B 100) and matrix fill (0.1 \ fill \ 0.9) was reached.…”
Section: Construction Of Random Benchmark Matricesmentioning
confidence: 99%
“…Dispersal also is favored by physical links between sites which can occur following heavy rainfall (Fahd et al 2007). As high connectivity is one of the main drivers of nestedness in biological communities (Boecklen 1997;Cook and Quinn 1995;Wright et al 1998;Higgins et al 2006) and dispersal has been suggested as being important in driving nested patterns (Patterson 1990;Atmar and Patterson 1993;Loo et al 2002;Hausdorf and Hennig 2003), we expected, and found, good dispersers to be more highly nested than poor and non-dispersing taxa (Cook and Quinn 1995). Isolation can affect the degree of nestedness observed across systems (Wright et al 1998;McAbendroth et al 2005;Monaghan et al 2005), something that we have observed in distant ponds located in northern and southern areas of the park, which had more idiosyncratic assemblages.…”
Section: Monthly Variation In Species Richness and Nestednessmentioning
confidence: 99%